2007
DOI: 10.1097/01.ta.0000235888.90489.fc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional Outcome After Unstable Pelvic Ring Fracture

Abstract: The long-term functional outcome after unstable pelvic ring fracture was not associated with Injury Severity Score, fracture location or fracture type. We discovered a close correlation between neurologic injury and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
5
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 23 publications
3
76
5
2
Order By: Relevance
“…Our data showed patients with complex pelvic fractures and patients treated operatively had a higher likelihood for a reduced quality of life. A literature search revealed two previous studies analyzing health-related quality of life in (Table 2) [2,24]. In a study population of 20 patients with unstable pelvic fractures treated by closed reduction and percutaneous fixation, Ayvaz et al [2] found an SF-36 score at 2 to 4 years postfracture comparable to that of population norms.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our data showed patients with complex pelvic fractures and patients treated operatively had a higher likelihood for a reduced quality of life. A literature search revealed two previous studies analyzing health-related quality of life in (Table 2) [2,24]. In a study population of 20 patients with unstable pelvic fractures treated by closed reduction and percutaneous fixation, Ayvaz et al [2] found an SF-36 score at 2 to 4 years postfracture comparable to that of population norms.…”
Section: Discussionmentioning
confidence: 94%
“…For elderly patients with pelvic ring fractures, several studies have reported substantial mortality, low short-term mobility, and frequent need for community support and institutionalization after discharge from hospital [10,16,17]. To our knowledge, only two studies on small populations of 20 and 57 patients have evaluated health-related quality of life after pelvic ring injuries, with conflicting results [2,24]. The impact of age on quality of life after pelvic ring fractures is unclear.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies focused on unstable pelvic fractures but did not distinguish between Tile B and C fractures [14,17,29,46]. A systematic review of the literature demonstrated better reduction quality, less pain, and improved undisturbed walking capacity for posterior pelvic ring fixation compared with nonoperative intervention [38].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been associated with worse functional outcome, including open fracture, sacroiliac joint disruption [8], urologic injury [16], neurologic injury [46], open reduction and internal fixation, residual posterior displacement [8,14,29], and psychological problems. Previous studies focused on unstable pelvic fractures but did not distinguish between Tile B and C fractures [14,17,29,46].…”
Section: Introductionmentioning
confidence: 99%